COMBINED SURGERY AND CHEMOTHERAPY FOR CANINE TRANSMISSIBLE VENEREAL TUMOR IN A FEMALE DOG: A CASE REPORT - Jihan Akifah; I Wayan Wirata; I Gusti Ngurah Sudisma (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Canine Transmissible Venereal Tumor (CTVT) is a neoplasia or tumor that can be transmitted through mating and physical contact such as licking, biting, kissing, or touching the tumor area. Canine Transmissible Venereal Tumor is a benign tumor that commonly affects both male and female dogs, with the external genital area as the main location of the tumor. A 1.5-year-old, 13.7 kg, mixed-breed female dog named